Tumor risks of finerenone in patients with type 2 diabetes mellitus complicated with chronic kidney disease: a meta-analysis and systematic review of randomized controlled trials - Du, Yue; Cao, Gui; Gu, Linlin; Chen, Yuehong; Liu, Jingyu (Frontiers in Pharmacology, 2024)
This study aimed to assess the tumor risk of finerenone in individuals with type 2 diabetes mellitus (T2DM) aggravated by chronic kidney disease (CKD). A thorough search in the OVID Medline, OVID EMBASE, and Cochrane Library databases from their creation through to November 2, 2022 yielded random controlled trials (RCTs) reporting on the tumor risks of finerenone in patients with T2DM complicated with CKD. A pair of reviewers selected the relevant studies based on selection criteria, collected data, and assessed the methodological quality of eligible RCTs. The Peto odds ratio (OR) with a 95% confidence interval (CI) was calculated, and subgroup analysis of tumor nature, tumor origin system, tumor origin organ, and follow-up time was performed. Furthermore, Egger's test was implemented to determine publication bias. Four randomized controlled trials with 14,875 participants who had a low-to-moderate risk of bias were included. Compared with placebo treatment, finerenone did not increase the risk of overall neoplasms (Peto OR=0.97; 95% CI, 0.83-1.14), malignant neoplasms (Peto OR=1.03; 95% CI, 0.86-1.23), benign neoplasms (Peto OR=0.94; 95% CI, 0.50-1.80), or in situ neoplasms (Peto OR=0.14; 95% CI, 0.01-2.17). Subgroup analysis of the tumor origin system showed that finerenone was associated with an increased risk of malignant neoplasms of urinary tract compared with placebo treatment (Peto OR=1.69; 95% CI, 1.07-2.67). The results were found to be robust in sensitivity analysis, and there was no indication of publication bias. Finerenone is not associated with an increased risk of overall tumors, but it may be linked to an increased risk of malignant neoplasms in urinary tract. Additional well-planned cohort studies in larger research populations are needed to corroborate these findings.